A survey of surgical patients’ perspectives and preferences towards general anesthesia techniques and shared-decision making - Bethany R. Tellor Pennington; Mary C Politi; Arbi Ben Abdallah; Allison M. Janda; Ingrid Eshun-Wilsonova; Nastassjia G. deBourbon; Lilly Siderowf; Heidi Klosterman; Sachin Kheterpal; Michael S. Avidan (BMC Anesthesiology, 2023)
Abstract Background The decision about which type of general anesthetic to administer is typically made by the clinical team without patient engagement. This study examined patients’ preferences, experiences, attitudes, beliefs, perceptions, and perceived social norms about anesthesia and about engaging in the decision regarding general anesthetic choice with their clinician. Methods We conducted a survey in the United States, sent to a panel of surgical patients through Qualtrics (Qualtrics, Provo, UT) from March 2022 through May 2022. Questions were developed based on the Theory of Planned Behavior and validated measures were used when available. A patient partner who had experienced both intravenous and inhaled anesthesia contributed to the development and refinement of the questions. Results A total of 806 patients who received general anesthesia for an elective procedure in the last five years completed the survey. 43% of respondents preferred a patient-led decision making role and 28% preferred to share decision making with their clinical team, yet only 7.8% reported being engaged in full shared decision making about the anesthesia they received. Intraoperative awareness, pain, nausea, vomiting and quickly returning to work and usual household activities were important to respondents. Waking up in the middle of surgery was the most commonly reported concern, despite this experience being reported only 8% of the time. Most patients (65%) who searched for information about general anesthesia noted that it took a lot of effort to find the information, and 53% agreed to feeling frustrated during the search. Conclusions Most patients prefer a patient-led or shared decision making process when it comes to their anesthetic care and want to be engaged in the decision. However, only a small percentage of patients reported being fully engaged in the decision. Further studies should inform future shared decision-making tools, informed consent materials, educational materials and framing of anesthetic choices for patients so that they are able to make a choice regarding the anesthetic they receive.